ANALISIS PRODUKTIVITAS TENAGA KERJA PEKERJAAN DINDING PADA PROYEK PEMBANGUNAN PENAMBAHAN RUANG KELAS BARU SMP NEGERI ALOK - Bernadeta Barek1; Margaretha Yuneta (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2024)
Labour productivity in the construction process is crucial for completing work according to the planned schedule because it has a significant impact on cost and time. Low labour productivity can lead to project delays and an extended overall project duration, increasing the project's cost. Therefore, it is necessary to conduct research on labour productivity in the New Classroom Addition Construction project at SMP Negeri Alok in this final project proposal. The data used for this rescarch were obtained through direct observation and field research. The analysis carried out is to find the value of actual labor productivity, plans and the Ministerial Regulation of PUPR08-2023 and its comparison. The results of this research obtained the actual productivity in the field for 1/2 brick wall work is 2.848493 m²/person for workers, 5.484205 m²/person for builders, and 9.917727 m²/person for the head builder and m. The planned productivity value is 3,333 m²/person for workers, 10 m²/person for handymen, 100 m²/person for handyman, and 66,667 m²/person for foremen. And the value of labor productivity according to the Minister of PUPR 08-2023 is 5 m²/person for workers, 10 m²/person for handymen, 100 m²/person for handymen, and 303,030 m²/person for foremen